Modern filter design active RC and switched capacitor - Ghausi, Mohammed Shuaib; Laker, Kenneth R. 1946- (Noble Publishing Corp., 2003)
Originally published in 1981, Modern Filter Design remains a classic statement of the principles underlying the analysis and design of active RC and switched capacitor filters. The book is a comprehensive tutorial on active filter design analysis and design procedures. This book covers: basic systems classifications together with filter transmission and approximations, operational amplifiers, including bipolar and MOS integrators, definitions of sensitivity and statistical sensitivity measures, continuous-time second-order active sections, higher-order filter design, and switched capacitor filters.